1994
DOI: 10.1111/j.1745-4549.1994.tb00237.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT of HEAT TREATMENT ON FIRMNESS of APPLES and APPLE SLICES

Abstract: Effects of heat treatment on firmness of apples (Golden Delicious, Mclntosh and Delicious) and apple slices were studied. Heat treatment (45C, for 1.75 h) of Golden Delicious and Delicious apples significantly increased their firmness, but no sign@cant increase was observed for the Mclntosh cultivar. After storage for 7days at 2C, the treated apples were firmer than those stored at 10, 18, and 25C. Apple slices prepared from the heat treated apples were also firmer at 21 days storage than those prepared from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…The combined use of heat treatments and minimal processing has been reported by Kim et al (1993Kim et al ( , 1994. Heating whole apples at 45°C every 30 min for a 2 h period before slicing improved the texture of apple slices as compared to nontreated apples, but this improvement depended upon cultivar.…”
Section: Effects Of Calcium Chloride Dips and Heat Treatmentsmentioning
confidence: 95%
“…The combined use of heat treatments and minimal processing has been reported by Kim et al (1993Kim et al ( , 1994. Heating whole apples at 45°C every 30 min for a 2 h period before slicing improved the texture of apple slices as compared to nontreated apples, but this improvement depended upon cultivar.…”
Section: Effects Of Calcium Chloride Dips and Heat Treatmentsmentioning
confidence: 95%
“…A marked reduction in softening was the main benefit obtained from heat treatment . However, some researchers reported that heat treatment had different effects on the firmness of apple fruits, including those of 'Jonagold' (Tu and De Baerdemaeker, 1997), 'McIntosh' (Kim et al, 1994) and 'Fuji' (Lunardi et al, 2003). From these results, it is clear that the effect of heat treatment on apple fruit firmness is cultivar-dependent.…”
Section: Comparative Effects Of Pre-storage Heat Treatment On Fruit Fmentioning
confidence: 97%
“…Softening of the tubers due to cooking is attributed to the physico-chemical changes occurring to the cell wall materials, such as reduction in hydrostatic pressure, gelatinization of starch and solubilization of pectic material in the middle lamella, cell separation, and an associated loss of turgor. [36][37][38][39][40] During thermal treatment, starch granules imbibe water and swell to a large extent, leading to the process called gelatinization, which occurs around 70-80 • C. [41] This will lead to the expansion of cell size and volume, cell separation, and cell wall distension depending upon the amount of starch content. [42,43] Sweet potato tubers contain heat stable amylases and it is active for a period during cooking until the temperature rises above about 70 • C and the starch gelatinizes; [15] however, they are inactivated at higher temperatures.…”
Section: Texture Profile Of Cooked Tubersmentioning
confidence: 99%